Patient-reported outcome survey of user-experiences in the spinal cord injured-community with MPPT for treating wounds and pressure injuries and for controlling soft tissue infection caused by osteomyelitis - Smith, Damian; Ridler, Mark (Frontiers in Rehabilitation Sciences, 2024)
BackgroundPeople with spinal cord injury (SCI) are at high risk of developing pressure injuries. Reports in the SCI-community had indicated that a new class of wound treatment, MPPT (micropore-particle-technology), was effective in treating pressure injuries. The British Spinal Injuries Association therefore conducted a survey among MPPT-users to learn from their experiences.MethodsOnline survey restricted to individuals with spinal cord injury. Participants were requested to identify themselves to permit validation of statement.ResultsThe survey had 41 respondents reporting on a total of 49 wounds of which the two main categories were wounds (n = 33), primarily pelvic pressure ulcers; and draining fistulas (n = 9) caused by osteomyelitis. All wounds reported had reached full closure. Median duration of MPPT use and time to closure were 3 and 4 weeks for acute wounds (<6 weeks old) and 8 and 10 weeks for chronic wounds, respectively. On draining fistulas, MPPT had been used to reduce wound size, remove soft tissue infection, avoid sepsis, reduce autonomic dysreflexia, improve overall health, and avoid bed rest, whilst waiting for surgery. Comments on MPPT were 84% highly positive, 11% positive, and 0% negative. No adverse events were reported.ConclusionsMPPT achieved a 100% closure rate of acute and chronic wounds, and, in draining fistulas, effectively controlled soft tissue infection resulting from osteomyelitis. MPPT does not require bed rest and is suitable for self-care and telemedicine, promoting independence and higher quality-of-life. The findings strongly agree with a recent clinical study of MPPT.